Adherence frequency of CANDIDA ALBICANS on nasoalveolar molding (NAM) appliances - CAN, BANU; YILMAZ, HANİFE NURAY; KADİR, TANJU (ELSEVIER, 2020)
Background and Method: The aim of this prospective study was to evaluate the adherence frequency of Candida albicans and non-albicans Candida species in newborn babies with Cleft Lip and Palate (CLP) who receive presurgical orthopedic therapy with Nasoalveolar Molding (NAM) appliances. This study comprised of 25 CLP newborns including 8-right unilateral, 8-left unilateral and 7-bilateral CLP. First swab samples were taken from the hard palate when the baby was referred and renewed after 3 days. Following the 7th day of delivery of NAM appliance, the swab samples were retaken from both the hard palate and the NAM appliance. Samples were renewed with 2-month intervals. The last swab samples were taken one month after the surgery. Oral swabs were cultured on CHROMagar Candida medium for the growth of yeasts. Results: There were no statistically significant differences between the time points regarding C. albicans proliferation frequency and severity rates on the palate. No significant difference was found due to the type of cleft and sex in terms of candidal colonization. A constant increase in proliferation frequency of non-albicans on the palatal mucosa was observed between all of the time points. Although the results were insignificant, there was a constant increase in C. albicans proliferation which presented a decrease following primary lip surgery. Conclusion: The appliance might not only cause an increase in the colonization of C. albicans but also provide the continuation of the colonization. Therefore, mouth cleaning is important even after primary lip surgery. (C) 2020 Elsevier Masson SAS. All rights reserved.
Keywords: Candida albicans; Cleft lip/palate; NAM therapy; BILATERAL CLEFT-LIP; ORTHODONTIC APPLIANCES; CARRIAGE; PALATE; THERAPY